2009
DOI: 10.5664/jcsm.27485
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Titration Polysomnogram on Treatment Success with a Mandibular Repositioning Appliance

Abstract: Scientific inveStigAtionSStudy Objectives: Mandibular repositioning appliance (MRA) therapy is a treatment option for patients with mild to moderate sleep apnea and for patients who do not tolerate continuous positive airway pressure. Titration of MRAs consists of sequential mandibular advancement guided by symptom improvement. The goal of the study was to determine if patients with an elevated apnea hypopnea index (AHI), despite the use of a subjectively optimized MRA, could achieve better results with additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 19 publications
2
36
0
9
Order By: Relevance
“…Our results are similar to those of other studies, 28,34,36,38,42,52 although there are authors who have reported worse results than ours, 35,37,39,40 perhaps because the sample size, BMI, and AHI were higher in these studies, and because of a certain degree of retrognathia in some patients. Better results than ours have been shown in other studies, 26,41,43,53 in our opinion due to a shorter follow-up, irregular use of a MAD, a larger sample, and inclusion of mild OSA in these studies.…”
Section: Effect Of the Mad On Polysomnographic Variablessupporting
confidence: 91%
“…Our results are similar to those of other studies, 28,34,36,38,42,52 although there are authors who have reported worse results than ours, 35,37,39,40 perhaps because the sample size, BMI, and AHI were higher in these studies, and because of a certain degree of retrognathia in some patients. Better results than ours have been shown in other studies, 26,41,43,53 in our opinion due to a shorter follow-up, irregular use of a MAD, a larger sample, and inclusion of mild OSA in these studies.…”
Section: Effect Of the Mad On Polysomnographic Variablessupporting
confidence: 91%
“…Apnea index (AI), apnea‐hypopnea index (AHI), minimum hemoglobin oxygen saturation measured by pulse oximetry (minimum SpO 2 ), and arousal index from overnight PSG data before and after treatment were used to evaluate treatment effects of the OA. In addition, treatment efficacy was evaluated based on goals of AHI < 10/h and a percentage reduction in AHI of more than 50% compared with baseline (Almeida et al ; Krishnan et al ; Kuna et al ).…”
Section: Methodsmentioning
confidence: 99%
“…24 A nonlinear dose-dependent relationship with degree of advancement is reported. [25][26][27][28][29][30] The efficacy of CPAP over MAD in reducing AHI is well established and has been consistently reported by meta-analyses comparing the 2, 4,31-34 even with increasing numbers of primary studies. According to the AASM/American Academy of Dental Sleep Medicine (AADSM) task force, CPAP is significantly better than MAD at reducing AHI scores (difference of 6.24 events per hour).…”
Section: Apnea-hypopnea Indexmentioning
confidence: 98%
“…After a clinical titration period, overnight MAD titration with PSG using the final MAD increased treatment response by an additional 9.9% to 30.4% of study subjects. 28,75 Disappointing outcomes were reported, however, using an interim MAD without a period of clinical titration because efficacy of the interim MAD was not translated to the final MAD. 76 Overnight MAD titration with PSG may require large single-night mandibular advancements to relieve respiratory events, in contrast to slow titration with conventional protocols.…”
Section: Therapeutic Diagnosismentioning
confidence: 99%
See 1 more Smart Citation